Dermoid cyst of the floor of the mouth in a young adult female: a case report - Alwakeel, Abdulaziz A.; Saad, Ali Mohammed; Dar, Samia Nawas; Alanazi, Abdullah M.; Alghabban, Abdulmohsen S. (International Journal of Research in Medical Sciences, 2026)
Dermoid cysts occur in the midline of the floor of the mouth, and they do not appear until they grow large enough or get infected. Rarely, they can be found in other areas beneath the oral mucosa such as jaw bone. This study aims to report a case of 20 years old female has large dermoid cyst in floor of mouth and increase the awareness of such lesion. A 20-year-old female presented to the oral and maxillofacial surgery clinic with a complaint of swelling in the floor of the mouth that had been increasing in size for approximately a year and a half. The patient was medically free and exhibited a notable ’double chin’ appearance. Clinical examination revealed a nodular lesion in the floor of the mouth. Radiographic evaluation demonstrated a well-defined radiolucent lesion approximately 6 × 3 cm in diameter, perforating the mylohyoid muscle. The differential diagnosis included dermoid cyst, lymphoepithelial cyst, and branchial cleft cyst. Excisional biopsy was done and Histopathological examination showed a cyst lined by keratinized stratified squamous epithelium containing sebaceous glands, confirming the diagnosis of a dermoid cyst. Dermoid cysts should be considered in the differential diagnosis of cystic lesions of the floor of the mouth. Accurate diagnosis relies on comprehensive clinical assessment, appropriate radiographic investigations, and definitive histopathological confirmation following complete surgical excision. Surgical management is associated with an excellent prognosis and a low risk of postoperative complications.